Фінансова безпека - необхідна умова функціонування підприємства - Пожуєва, Т.О. (Вісник економічної науки України, 2014)
У статті розглянуті найбільш поширені визначення фінансової безпеки, проаналізовано сильні та слабкі сторони цих тлумачень. Також виокремлено умови забезпечення фінансової безпеки підприємства. Крім того, розглянуто принципи, дотримання яких уможливлює фінансову безпеку підприємства та висвітлено низку функцій, які має виконувати система фінансової безпеки. В статье рассмотрены наиболее распространенные определения финансовой безопасности, проанализировано сильные и слабые стороны этих толкований. Кроме того, рассмотрено принципы, соблюдение которых делает возможной финансовою безопасность предприятия и показано ряд функций, которые должна выполнять система финансовой безопасности. We are monitoring the most expanded definitions of Financial Safety, and have analyzed the ones’ strength and weakness in the thesis. We have monitored some particular studies by the scientists - the economists dealt in the field. The Author has admitted a lack and necessity of a single proved and confirmed approach to the term of «Financial Safety» term. Therefore the «Financial Safety» term has to include sense of the Enterprise’s Financial Safety, simultaneously it has to reflect overall Public Financial Safety Environment with the help of equilibrated and qualitative characteristics of systematic set of financial tools, technologies and services, steadiness to the internal and external negative factors (threats), ability of the environment to provide financial interests protection, sufficient volumes of financial resources for all economical subjects and the population. So it’s worth to compare other scientist’s approaches to avoid misunderstandings concern Safety definition. The terms of Financial Safety Provision is localized. Moreover we have monitored the the background of both Enterprise’s Financial Safety and Public Financial Safety. We have proved that the Financial Safety Management expects unification of the related scientific theories, concepts, strategies, tactics and adequate financial police execution.